2010
DOI: 10.1086/653579
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Rotavirus Diarrhea in Countries in the Eastern Mediterranean Region

Abstract: This systematic review of studies of rotavirus diarrhea among children in the countries of the Eastern Mediterranean Region documents that rotavirus is one of the most significant causes of childhood diarrhea in the region. The findings of this review will be used to establish sentinel hospital surveillance in these countries, estimate disease burden, and characterize its epidemiology using common protocols and diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
35
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
13
35
0
2
Order By: Relevance
“…As previously observed in the Eastern Mediterranean region [18][19][20][21] and Europe, 22 we found the burden of RVGE to be the highest in children younger than 2 y. More specifically, RVGE was found predominantly in the 7-12 mo age group in a study conducted in 1994 in UAE (34.8%).…”
Section: Discussionsupporting
confidence: 83%
“…As previously observed in the Eastern Mediterranean region [18][19][20][21] and Europe, 22 we found the burden of RVGE to be the highest in children younger than 2 y. More specifically, RVGE was found predominantly in the 7-12 mo age group in a study conducted in 1994 in UAE (34.8%).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, children hospitalized for diarrhoea were more likely to have RVA detected (24.9 %) than those consulting as outpatients (18.5 %), confirming that RVA gastroenteritis is usually more severe than non-RVA diarrhoea (El-Shabrawi et al, 2015; Malek et al, 2010).…”
Section: Rva Detection Ratesupporting
confidence: 78%
“…The detection rate of rotavirus is 40% in the eastern Mediterranean region, while a higher level was found in Asia with 45% and lower in Latin America and Africa with 38% and 24% respectively. [16][17][18] This was consistent to the studies by Parasher et al 5 A much higher rate compared to our study was reported by Taqbo et al of 56% rotaviral incidence in children below 5 years of age. 9 In India, an incidence of 34% was reported in various studies.…”
Section: Discussionsupporting
confidence: 93%